Algoritma Pemrograman Berbasis MCS-51 Untuk Simplifikasi Rangkaian Driver Alphanumeric-Liquid Crystal Display(LCD): Programming Algorithm on MCS-51 for Alphanumeric Liquid Crystal Display(LCD) Simplified Driver Circuit - Son, Putut; Susianti, Elva (Indonesian Journal of Electrical Engineering and Renewable Energy (IJEERE), 2022)
Wiring between microcomputer(minimum system either microcontroller) and alphanumeric LCD on 8 bit standart mode requires 11 pins. Assignment on large number of I/O pins designated for LCD interfacing is inefficient and unsuitable when applied for compact microcontroller AT89C2051 which has only 15 I/O pins. Interfacing to LCD can be simplified using I2C LCD KIT with additional cost and reconfiguring the functionality of I/O as consequences. The availability of library as a driver program on IDE compiler is uncertain since there are many brands compete on microcomputer as their product. This research exhibits serial to parallel method to simplify and save I/O resources utilizing a digital 74595 functional logic into a script of program to drive and communicate with LCD. The algorithm was tested on VSM Proteus application program and result shows a good agreement between design and visualization.This study has shown that the wiring technique and algorithm works well yielding 72.2% more efficient compared to standard wiring.